Divine Enjoyment: A Theology of Passion and Exuberance, by Elaine Padilla - McCall, Bradford ca. 21. Jh. (Religious studies and theology, 2016)
Divine Enjoyment: A Theology of Passion and Exuberance, by Elaine Padilla. Fordham University Press, 2014. ix + 296 pp,, $27.00. ISBN-13: 9780823263578